The Impact of Applying International Financial Reporting Standards (IFRS) on the Quality of Financial Reports: The Mediating Role of Accounting Disclosure in Banks Operating in the Iraq Stock Exchange - Haider Seher (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
This research aims to study the advantages of applying International Financial Reporting Standards (IFRS) in economic units, as well as to evaluate the impact of these standards on the quality of financial reports. The study utilized publicly available information from companies listed on the Iraq Stock Exchange. A checklist was developed to assess the extent of adoption of these standards. Furthermore, statistical techniques were employed to test the study's hypotheses. The study results showed that adopting international standards in accordance with accounting disclosure requires sufficient knowledge from those working with it in order to reflect on the quality of information. The results of the survey from the sample surveyed showed the importance of international standards for preparing financial reports, which helps in the quality of accounting information through disclosure. It is accepted that international standards play an important role in improving the quality of accounting information in banks operating in the Iraq Stock Exchange. The study also called for a focus on training accountants in the Iraq Stock Exchange and other entities that adhere to these standards, given their importance and ability to enable accountants to perform their work accurately and efficiently. It also encouraged other economic entities to adopt these standards. The application of International Financial Reporting Standards (IFRS) is witnessing continuous growth due to its pivotal role in economic entities, enhancing the quality of accounting information.